In Situ Fabrication of Tungsten Diphosphide Nanoparticles on Tungsten foil: A Hydrogen‐Evolution Cathode for a Wide pH Range. Issue 9 (19th July 2016) - Pu, Zonghua; Amiinu, Ibrahim Saana; Mu, Shichun
Abstract: Identifying non‐precious metal electrocatalysts for the hydrogen‐evolution reaction (HER) with high efficiency and stability is a considerable challenge for the hydrogen‐based energy industry. We report the preparation of WP2 nanoparticles supported on W foil (WP2 NPs/W) through phosphidation of the corresponding WO3 NPs/W precursor. This hydrogen evolution cathode shows a high HER catalytic activity with a low overpotential ( j >100 mA cm −2 at η =211 mV), a small Tafel slope (66 mV dec −1 ), and a large exchange current density (0.09 mA cm −2 ) as well as excellent stability over 27 h in acidic solution. Notably, this catalyst also offers superior catalytic activity and remarkable stability under neutral and alkaline conditions. It is worth noting that, as a Pt‐free HER catalyst, WP2 NPs/W shows an electrocatalytic activity comparable to reported noble metal‐free HER electrocatalysts at all pH values. Thus, the in situ conversion method provides a pathway to fabricate highly efficient and low‐cost as well as self‐supported non‐precious‐metal electrodes for HER. Abstract : This can do all : Tungsten diphosphide nanoparticles supported on tungsten foil are synthesized using a two‐step strategy. They are used as an electrocatalyst for hydrogen evolution reaction, exhibiting excellent catalytic activity and stability over a wide pH range.